1981 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1981)

Le comité régional (Montreal) du Congrès national des femmes noires : Rapport - Le Comite Regional (Montreal) du Congres National des Femmes Noires (1981)
Les buts de cette conference etaient de sensibiliser le public en general (Noir et Blanc) c'est-a-dire, les parents et les enfants, les etudiants et les enseignants, les organisations gouvernementales et para-publiques au racisme et au sexisme, qui existent dans les manuels scolaires de trouver des solutions aces problemes et d'utiliser notre force collective afin d'effectuer les changements sociaux constructifs.

National Regional Committee National Congress of Black Women Report - Montreal Regional Committee National Congress of Black Women (1981)
The objectives of this Conference were aimed at sensitizing the general public (Black and White) i.e. parents and children, students and teachers, governmental and para-public organizations, to the racism and sexism found in the textbooks used in our school system, to develop solutions to these problems and to use our collective strength to bring about constructive social change.